Development of Reading and Numeracy Literacy Assessment Instrument in Electrolyte and Non-Electrolyte Solutions for Critical Thinking Skills - Amelia Ineza Karima; Triannisa Rahmawati; Wiwi Siswaningsih; Nahadi Nahadi (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2026)
The development of assessment instruments that can measure reading literacy, numeracy literacy, and critical thinking skills is still a necessity in chemistry learning. This study aims to develop reading literacy and numeracy assessment instruments to measure critical thinking skills in the material of electrolyte and non-electrolyte solutions. This study used a test design and development method based on the Standards for Educational and Psychological Testing. The instrument was validated by five experts and tested on 21 tenth-grade high school students. Data analysis included content validity (CVR), empirical validity (Pearson Product Moment), reliability (KR-20 and Cronbach's Alpha), difficulty level, and distinguishing power. The results showed excellent content validity, with CVR values of 0.992, 1.000, and 0.968, respectively. Of the 35 items, 23 (65.71%) were empirically valid. The reliability coefficients were 0.70 for multiple choice, 0.93 for essay, 0.72 for complex multiple choice – true/false, and 0.15 for matching. The difficulty level was dominated by the moderate category (57%). distinguishing power shows that 55% of the test items are in the fair to good category. Overall, the instrument met most of the quality criteria and showed potential for assessing reading comprehension, numeracy, and critical thinking skills, although further improvements were suggested.